Combined Management of Colon Cancer Local Recurrences with Using Intraabdominal Chenotherapy - A. P. Zhuchenko; A. F. Filon; I. D. Kalganov; M. S. Likhter (Антибиотики и Химиотерапия)
The efficacy of intraabdominal chemotherapy in management of local recurrences of colon cancer was studied. Intraabdominal intraoperative and early postoperative chemotherapy made it possible to prolong of the recurrenceless term and to improve the life quality of the patients with local recurrences of colon cancer. There was observed a tendency to increase the five-year survival.